THE STUDY OF STUDENTS’ INTOLERANCE IN LITHUANIA AND GERMANY. COMPARATIVE ANALYSIS - Bumblauskaitė, Jogailė; Lepeškienė, Vitalija; Paškauskaitė, Aistė (Socialinė teorija, empirija, politika ir praktika, 2007)
The goal of the paper is to compare student’s tolerance in Lithuania and Germany. The lack of tolerance raises violence and aggression. The targets of aggression usually are groups of individuals in social exclusion. The people in social exclusion are disable, women, ethnic minorities and other. These groups are clients of social work. To reveal the attitude towards toleration and experience in violence and discrimination, the survey was conducted. The respondents were students. The data analysis suggests that Lithuania students are less tolerant in comparison to Germany. There are significant differences in the attitude towards ethnic minorities, sexual minorities and homeless.